Comparative evaluation of effect of green tea and green coffee on blood cholesterol level and body weight in albino rats - Kumar, Ratan; Purty, Manoj Kumar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Overweight and obesity are chronic medical condition responsible for risk factors for many non-communicable diseases. Development of rapid upsurge of these condition in medium and low-income group countries increased the awareness and uses of many types of remedies. Along with other natural herbal products green tea and green coffee have also became popular in communities. Aim of this study was to compare the effect of green tea and green coffee on blood cholesterol and weight in experimental animals. Methods: The experiment of this study was conducted in the Department of Pharmacology, MGM Medical college, Jamshedpur after ethical approval. 24 albino rats were selected and divided randomly in four groups A B C D. Group ‘A’ was kept as control group, group ‘B’ was given fat rich diet to produce hypercholesterolemia, group ‘C’ and ‘D’ were given green tea and green coffee respectively along with cholesterol rich diet. Weight and cholesterol level of rats were measured on 1st day, 2nd week and 4th week. Results: There was significant increase in serum cholesterol in non-treated animals as compared to control group but parameter showed significant less rise of cholesterol and weight in treated group by both green tea and green coffee than non-treated group. The comparative effect of green tea and green coffee had not much difference. Conclusions: This study has provided the information that natural products like green tea and green coffee are useful and helpful in preventive therapy of dyslipidemia and obesity.